2016
DOI: 10.1007/s11842-016-9335-0
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Patterns of Fuelwood in Rural Households of Dolakha District, Nepal: Reflections from Community Forest User Groups

Abstract: Biomass plays a vital role in the energy supply of many developing countries. It is the major energy source for the rural population of Nepal, where 70 % of the total energy is derived from woody plant biomass in the form of fuelwood. The main aim of this study is to describe the fuelwood consumption pattern and the role of community forests and trees on private farmland in biomass supply to rural households in Nepal. The study investigates whether demography and socioeconomic attributes of households affect f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 32 publications
(49 reference statements)
3
28
3
Order By: Relevance
“…Household size with less than 3 member consumed 5240 kg firewood, 3-4 household size consume 8440 kg and household size 5 and above consume 9400 kg firewood annually.There is lack of data for comparative analysis of percapita daily firewood consumption from Mountain region. The Forestry Sector Master Plan reported that the annual per capita firewood consumption ranges from 480kg to 600 kg in Hill and Mountain region (MPFSP, 1989;Kandel et al, 2016). However, results of this study shows higher amount (2200kg) of annual per capita consumption.…”
Section: Tourism Development and Firewood Consumptioncontrasting
confidence: 60%
“…Household size with less than 3 member consumed 5240 kg firewood, 3-4 household size consume 8440 kg and household size 5 and above consume 9400 kg firewood annually.There is lack of data for comparative analysis of percapita daily firewood consumption from Mountain region. The Forestry Sector Master Plan reported that the annual per capita firewood consumption ranges from 480kg to 600 kg in Hill and Mountain region (MPFSP, 1989;Kandel et al, 2016). However, results of this study shows higher amount (2200kg) of annual per capita consumption.…”
Section: Tourism Development and Firewood Consumptioncontrasting
confidence: 60%
“…While our data did not show any detectable influence of wood extraction on panda occurrence, we note that fuel wood is still a dominant form of energy use in mid hills of Nepal, including Dhorpatan [62,63]. Small-scale urbanization in the region [64] has led to increased demand for timber for construction [65].…”
Section: Discussionmentioning
confidence: 97%
“…This diversity is the very basis for rural livelihoods in the Middle Hills of Nepal, as it provides vital ecosystem services such as fuelwood, timber, livestock fodder, and edible, aromatic and medicinal plants, in addition to harbouring important functions like securing water quality and flow regulation, carbon sequestration, erosion control, and regional climate regulation [10,[14][15][16][17][18]. Traditional sources of energy including fuelwood, agricultural residues, and animal dung dominate the energy sector in Nepal and constitute 84% of the total energy consumption (fuelwood alone contributes 75%) [19,20], as 83% of Nepal's population lives in rural areas where fuelwood is the dominant source of energy [21]. Approximately 40% of the livestock in the Middle Hills is fed with leaf fodder from ca 100 tree species [22], and oak species are the most heavily exploited [15,23,24].Unregulated resource extraction is a major threat faced by many forested areas in Nepal.…”
mentioning
confidence: 99%